Net Community Production in the Southern Ocean: Insights From Comparing Atmospheric Potential Oxygen to Satellite Ocean Color Algorithms and Ocean Models. Issue 19 (10th October 2018) - Nevison, Cynthia; Munro, David; Lovenduski, Nicole; Cassar, Nicolas; Keeling, Ralph; Krummel, Paul; Tjiputra, Jerry
Abstract: The contribution of oceanic net community production (NCP) to the observed seasonal cycle in atmospheric potential oxygen (APO) is estimated at Cape Grim, Tasmania. The resulting APONCP signal is compared to satellite and ocean model‐based estimates of POC export and NCP across the Southern Ocean. The satellite products underestimate the amplitude of the observed APONCP seasonal cycle by more than a factor of 2. Ocean models suggest two reasons for this underestimate: (1) Current satellite products substantially underestimate the magnitude of NCP in early spring. (2) Seasonal O2 outgassing is supported in large part by storage of carbon in DOC and living biomass. More DOC observations are needed to help evaluate this latter model prediction. Satellite products could be improved by developing seasonally dependent relationships between remote sensing chlorophyll data and in situ NCP, recognizing that the former is a measure of mass, the latter of flux. Plain Language Summary: Phytoplankton in the surface ocean transform carbon dioxide into organic carbon while also producing oxygen. A fraction of the carbon is exported into the deep ocean, while the oxygen is emitted to the atmosphere. The carbon export rate influences how much carbon dioxide the ocean can absorb. The rate is commonly estimated using satellite‐based phytoplankton color measured in the surface ocean, but such estimates involve many uncertain steps and assumptions. Small but detectible seasonal cycles in atmospheric oxygen have been used as an independent method for evaluating satellite‐based estimates of organic carbon export. In this study, we evaluate eight satellite‐derived carbon export estimates based on their ability to reproduce the observed seasonal cycle of atmospheric oxygen measured at a southeastern Australia site. All underpredict the seasonal oxygen cycle by at least a factor of 2, in part because they fail to capture the carbon and oxygen produced in early springtime and also because they focus on large particles of carbon that are heavy enough to sink while neglecting the dissolved fraction of organic carbon. Our study suggests that satellite estimates could be improved by a better understanding of seasonal variations in the relationship between phytoplankton productivity and carbon export. Key Points: Ocean models suggest that net DOC production contributes significantly to NCP, O2 outgassing, and carbon export in the Southern Ocean The observed APONCP cycle supports the model results and suggests that satellite‐based estimates underestimate the seasonal amplitude of NCP The underestimate is due in part to early spring NCP, which is not well represented by in situ and satellite‐based approaches